Psycholinguistic Universals of Comprehending the Prayer "Our Father" (Discursive Approach) - Savelyuk, Nataliia (East European Journal of Psycholinguistics, 2017)
The author grounds empirically and theoretically a discursive approach to the study of the features of comprehending a prayer as a basic genre of religious discourse. Religious discourse is viewed as an active reception, transmission and/or creation (co-creation) of religious texts in their specific contexts (broad social, including communicative and individual settings). It is associated with the construction of religiously relevant discursive models of reality and its components in accordance with respectively oriented concepts and utterances (statements). Therefore, selection, formulation of such utterances and their comprehension are treated as the consequence of the appropriate active choices of the subject of religious discourse (individual or collective). In this regard, it is substantiated that a prayer includes not only the system of its generalized, traditional meanings (theological and linguistic levels of analysis), but also individual, contextually conditioned perception and comprehension by its specific subject (psychological and psycholinguistic levels of analysis). The conceptual basis of the empirical research is the discursive approach. The methodical basis is psycholinguistic text analysis. The fundamental methods and techniques are “The measuring technique of religious activity” by D.O. Smirnov and the content analysis of the recorded religious discourses. Due to the analysis of the canonical prayer “Our Father” and the forthcoming religious discourses (products of its comprehension) of the respondents with different levels of religious activity (low, below average, above average, high), the author defines basic categories through which the comprehension of such discourse takes place: 1) “Being and its common attributes”; 2) “God, His name and attributes”; 3) “A Person and his/her everyday existence”; 4) “Prayer and its components”; 5) “Good (spiritual)”; 6) “Forbidden (sinful)”. The following general trends (from the lowest to the highest levels of religious activity) are also stated: significant increase (the amount of words, the amount of sentences and the average amount of words in a sentence), insignificant increase (indicators of emotional intensity) and decrease (indicators of lexical diversity and lexical density of religious discourses of Ukrainians).ReferencesЗасєкін С. Психолінгвістичні універсалії перекладу художнього тексту: монографія.Луцьк: Волин. нац. ун-т ім. Лесі Українки, 2012.Zasiekin, S. (2012). Psykholinhvistychni Universalii Perekladu Khudozhnoho Tekstu[Psycholinguistic Universals in the Translation of Literary Texts]. Lutsk: Volyn StateUniversity.Серкин В.П. Методы психосемантики: Учеб. пособие для студентов вузов. М.:Аспект-Пресс, 2004.Serkyn, V.P. (2004). Metody Psikhosemantiki [The Methods of Psychosemantics]. M.:Aspekt-Press.Смирнов Д.О. Описание процедуры стандартизации психометрической методики«Опросник религиозной активности» // Научный психологический журнал. 1999. C.1–2. Smirnov, D.O., (1999). Opisaniye protsedury standartizatsii psikhometricheskoi metodiki“Oprosnik relihioznoi aktivnosty” [Description of Procedure of the Psychometric Method’s“The Measuring Technique of Religious Activity” Standardization]. NauchnyiPsikholohicheskii Zhurnal, 1–2, 159–172.Спилка Б., Лэдд К. Л. Психология молитвы. Научный подход. Харьков:Гуманитарный центр, 2015.Spilka, B., Ladd, K. L. (2015). Psikholohiya Molitvy. Nauchnyi podkhod [The Psychologyof Prayer: A Scientific Approach]. Kharkiv: Humanitarnyi Tsentr.